Two-stage management of a spontaneous fracture of the greater trochanter through osteolytic lesions induced by polyethylene wear of a total hip arthroplasty. A case report - Regis, Dario; Sandri, Andrea; Samaila, Elena; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2019)
Pelvic osteolysis induced by particulate debris derived from bearing surfaces is a well-known complication following total hip arthroplasty (THA). Atraumatic fractures of the greater trochanter (GT) associated with osteolytic lesions have been occasionally described. We present a case of a 71-year-old male patient who sustained an undisplaced fracture of the GT nine years following cementless metal-on-polyethylene THA. The fracture occurred through a 2.5-cm large osteolytic area, and no hip trauma was recorded. Conventional radiographs revealed peculiar signs of massive wear of the polyethylene acetabular liner (marked eccentricity of the prosthetic head and extensive osteolysis around the iliac screws), allowing to immediately conclude about the benign nature of the pathological fracture. To our knowledge, a two-stage management, planning conservative healing of the fracture and subsequent surgical replacement of the worn acetabular liner, has never been previously detailed.